A damage threshold prediction model of CFRP panel by hail impact based on delamination mechanism - Liu, Kai; Liu, Jia Long; Wang, Zhonggang (Engineering fracture mechanics, 2020)
•A numerical model is established for simulating CFRP impacted by hail ice.•A damage threshold prediction model of CFRP impacted by ice ball is proposed.•A CFRP damage threshold can be derived at lower cost. Dynamic response mechanism of CFRP (Carbon Fiber Reinforced Polymer) panel under high-speed ice ball impact was challenging to elucidate due to inherent heterogeneity and anisotropy properties. This further leads to difficulties in theoretical prediction of the damage threshold. Simulation modelling of CFRP panel subjected to high-speed ice ball impact was conducted in this study. Through coupling SPH (Smoothed Particle Hydrodynamics) and FEM (Finite Element Method), the simulation has captured the deformation and damage of the CFRP panel and ice ball. A damage threshold prediction model of CFRP was then proposed based on the mechanism analysis of the dynamic deformation and delamination. The traditional prediction of CFRP impact damage threshold, that is, parametric studies on the damage threshold of CFRP panel influenced by different impact speed, ice ball diameter and panel thickness was performed. Finally, the results show that the CFRP damage threshold law obtained from parameterized simulation matches the previous experimental results, and a conservative damage threshold can be predicted from the proposed theoretical model. The proposed theoretical model can contribute to predicting the damage threshold of CFRP panels subject to ice ball impacts at low cost.